Relationship Usage Behavior and Utilization of Media Information By Dairy Farmers - Zulkarnaen, Givary Apriman; Riyanto, Sutisna (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2017)
Media information is currently undergoing rapid development with increasingly widespread use to the rural. The study aims to see the relationship between members of dairy cattle group in Cibogo Village as the characteristics of breeders based on the individual and the environment, the motive of the use of information media, and the behavior of media use with the utilization of information media for livestock activities based on Sapta Usaha Peternakan. This research was conducted with quantitative approach using survey method to 40 breeders supported by qualitative data. The use of information media by breeders is high, with duration and high frequency with more than one type of media. Characteristics of individual ranchers and farmer's environments have a noticeable relation to the part of formal education and social condition. Motive use of information media with motive information, social, identity, and entertainment on the breeder is high and has a real relationship with media usage behavior. Utilization of media in the field of agriculture is seen in the section cage and seed management.Keywords: characteristics of breeders, motive of media usage, sapta usaha peternakan=============================================== ABSTRAKMedia Informasi saat ini mengalami perkembangan yang pesat dengan pemanfaatan yang semakin luas hingga ke pedesaan. Penelitian bertujuan untuk melihat hubungan antara anggota kelompok ternak sapi perah di Desa Cibogo seperti karakteristik peternak berdasarkan individu dan lingkungan, motif penggunaan media informasi, dan perilaku penggunaan media dengan pemanfaatan media informasi untuk kegiatan peternakan berdasarkan Sapta Usaha Peternakan. Penelitian ini dilakukan dengan pendekatan kuantitatif menggunakan metode survei terhadap 40 peternak didukung oleh data kualitatif. Penggunaan media informasi oleh peternak sudah tinggi, dengan durasi dan frekuensi yang cukup tinggi dengan lebih dari satu jenis media. Karakteristik peternak individu dan lingkungan peternak memiliki hubungan nyata terlihat pada bagian pendidikan formal dan keadaan sosial. Motif penggunaan media informasi dengan motif informasi, sosial, identitas, dan hiburan pada peternak sudah tinggi dan memiliki hubungan nyata dengan perilaku penggunaan media. Pemanfaatan media pada bidang peternakan terihat pada bagian perkandangan dan pengelolaan bibit.    Kata Kunci : Karakteristik peternak, motif penggunaan media, sapta usaha peternakan